mRNA therapeutics in cancer immunotherapy - Beck, Jan D.; Reidenbach, Daniel; Salomon, Nadja; Sahin, Ugur; Türeci, Özlem; Vormehr, Mathias; Kranz, Lena M. (Molecular cancer, 2021)
Synthetic mRNA provides a template for the synthesis of any given protein, protein fragment or peptide and lends itself to a broad range of pharmaceutical applications, including different modalities of cancer immunotherapy. With the ease of rapid, large scale Good Manufacturing Practice-grade mRNA production, mRNA is ideally poised not only for off-the shelf cancer vaccines but also for personalized neoantigen vaccination. The ability to stimulate pattern recognition receptors and thus an anti-viral type of innate immune response equips mRNA-based vaccines with inherent adjuvanticity. Nucleoside modification and elimination of double-stranded RNA can reduce the immunomodulatory activity of mRNA and increase and prolong protein production. In combination with nanoparticle-based formulations that increase transfection efficiency and facilitate lymphatic system targeting, nucleoside-modified mRNA enables efficient delivery of cytokines, costimulatory receptors, or therapeutic antibodies. Steady but transient production of the encoded bioactive molecule from the mRNA template can improve the pharmacokinetic, pharmacodynamic and safety properties as compared to the respective recombinant proteins. This may be harnessed for applications that benefit from a higher level of expression control, such as chimeric antigen receptor (CAR)-modified adoptive T-cell therapies. This review highlights the advancements in the field of mRNA-based cancer therapeutics, providing insights into key preclinical developments and the evolving clinical landscape.